The structural modelling of significant organisational and individual factors for promoting sustainable campus in Saudi Arabia - Alsharif, Mohammad Ambarak (Frontiers in Sustainability, 2024)
campus sustainability has risen to global prominence, with sustainability and environmental activities being key components used as yardsticks rather than benchmarks or points of comparison to determine comparative institutional advantage. The focus of this paper is to explore the factors that contribute to the expansion of sustainability initiatives and practices within university campuses in Saudi Arabia. Using the Interpretive Structural Model (ISM) as a paradigm for public universities, this study explores the impact of organizational factors and individual-related factors on the implementation of sustainable practices. The research is based on a literature review, incorporating rational choice theory (RCT) and organizational change theory (OCT) to identify variables relevant to campus sustainability. It focuses on the hierarchical interrelationships among these variables and proposes solutions for integrating sustainability-related actions and practices on university campuses. The employment of the ISM is aiming to establish links between the identified variables, validating the associations through consultations with experts from selected case study institutions. Additionally, the Matrice d'Impacts Croises-Multiplication Appliqué and Classment Analysis (MICMAC) categorize the study variables. The findings emphasis the significance of organizational structure and decision-making process in determining the prevalence of other variables. Consequently, these two variables were considered key in that exert significant influence over the others, which necessitates rapid attention. Furthermore, because of its great driving and reliance power, leadership was categorised as a linkage variable, which represented a strong relationship within the hierarchical model. The study recognizes the challenges faced in implementing sustainability initiatives, including conflicts in strategic planning, absence of campus sustainability policies and regulations, financial barriers, and lack of support from leadership. These findings can assist stakeholders involved in implementing sustainability initiatives in higher education institutions (HEIs), particularly university leaders and decision makers in facility and project management (F&PM) departments, in designing effective platforms for communicating sustainability-related actions and practices. The main contribution of the paper is to offer valuable insights and recommendations for stakeholders involved in the implementation of sustainability initiatives in higher education institutions (HEIs). Specifically, the focus is on university leaders and decision makers in facility and project management (F&PM) departments.